Croatian Logistics : Opportunities for Sustainable Competitiveness - Blancas, Luis C. (World Bank, Washington, DC, 2021)
Croatia needs to find new sources of economic growth to attain income convergence with the EU; this was true before the onset of the coronavirus disease 2019 Coronavirus (COVID-19) pandemic, and it is an even more urgent challenge now. Improvements in freight logistics, which permeate the tradeable economy and domestic commerce, can become a catalyst of productivity growth, business resilience, and environmentally sustainable economic expansion for Croatia. Efficient logistics facilitate trade by improving access to markets through connectivity improvements and cost competitiveness. This report takes stock of Croatia’s logistics sector at the national level. It aims to describe the sector’s supply-demand composition, identify challenges and opportunities to improve sectoral performance, and recommend public policy measures to address these challenges and meet the opportunities at hand.